Frente libertario de Venezuela: La lucha por la segunda independencia nacional - Flor María Ávila Hernández, Jesús Caldera Ynfante, Alejandro Castaño, (Opción, 2020)
Se investiga sobre la situación de Dominación Extranjera Consentida (DEC) en Venezuela y se detallan elementos de la subyugación del pueblo venezolano por el régimen autoritario cubano. Se aborda el estudio del Frente Libertario de Venezuela (FLV)1 en la lucha por la emancipación del pueblo y la posible activación de un FLV atípico, destacando su reconocimiento como sujeto de derecho internacional con el objetivo de i) se considere representante legítimo del pueblo venezolano; ii) ejecute actividades de socorro y asistencia a la población afectada por la emergencia humanitaria compleja y iii) actúe como Observador ante organismos internacionales, sin renunciar a los medios de la desobediencia civil y la rebelión popular derivados del derecho a la libre determinación y del derecho-deber de resistencia.  AbstractReflects on the situation of Consented Foreign Dominance (DEC) in Venezuela and details some elements that define the circumstance of subjugation of the Venezuelan people by the Cuban authoritarian regime, addresses the study of the Libertarian Front of Venezuela (FLV) as a political and legal instrument in the struggle for the emancipation of the dominated people and on the possible activation of an atypical FLV or sui generis in function of the Second Independence of Venezuela, highlighting its recognition as a subject of international law - legal status - with the aim of i) being considered legitimate representative of the Venezuelan people; ii) carry out relief and assistance activities for the population affected by the complex humanitarian emergency generated by the dictatorial regime of Nicolás Maduro Moros; and iii) act as an Observer before states and international organizations as a vehicle to overcome the DEC situation suffered by the Venezuelan people , without claiming the international quality of belligerent status, fighting nonviolently, peacefully and without weapons, without renouncing the means allowed by civil disobedience and popular rebellion (including civic-military) derived from the activation of the right of Venezuelans to self-determination and the right-duty of resistance to oppression as an affirmation of their human dignity within the framework of International Humanitarian Law.